PENGARUH METODE BERMAIN PERAN TERHADAP KEPERCAYAAN DIRI ANAK DI RA DWP KEMENAG - Arsawalnisah, Arsawalnisah; Miranda, Dian; Amalia, Annisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study aims to investigate the application of role-playing methods to develop self-confidence in children aged 5-6 years at RA DWP Kanwil Kemenag. This research uses a qualitative approach with descriptive methods. The participants in this study are the head and teachers of RA DWP Kanwil Kemenag. The data analysis technique employs qualitative analysis through data reduction, data presentation,and conclusion drawing. The results show that the application of roleplaying methods effectively increases the self-confidence of children aged 5-6 years through proper preparation and instructions, direct action in the play, and in-depth evaluation of the students' progress. This supports the development of children's self-confidence through comprehensive and meaningful learning experiences at RA DWP Kanwil Kemenag. Teachers clearly choose role-playing situations that match the children's needs, provide instructions on role characteristics, and conduct warm-up exercises before starting the play. This helps students develop imagination and group cohesion. Students actively engage in role-playing with confidence and enthusiasm, then participate in reflective discussions to understand and respond to the experiences they have had. This supports the development of a deeper understanding of themselves and social relationships, as well as critical thinking skills. Teachers evaluate by observing student interactions during the play and providing constructive feedback, as well as planning relevant follow-up activities to reinforce their selfconfidence. This evaluation helps identify students' progress in selfconfidence, optimistic attitudes, responsibility, and rational and realistic thinking.